Elevated Levels of Gonadotrophic Hormones and Antioxidant Biomarker in Male Rats Following Administration of Hydromethanol Leaf Extract of Justicia secunda in Response to 2,4-Dinitrophenylhydrazine Induction - Samuel Kelechi Mobisson; Uchechukwu Loveth Iyanyi; Ben Enoluomen Ehigiator; Fidelis U. Ibe; Justin Bonaparte Monye; Agona O. Obembe (Wolters Kluwer Medknow Publications, 2024)
Background: 2,4-Dinitrophenylhydrazine induces testicular toxicity and can result in reproductive dysfunction in male rats. Aim: This study investigated the effects of hydromethanolic leaf extract of Justicia secunda on phenylhydrazine (PHZ)-induced reproductive dysfunction in male Wistar rats. Settings and Design: Twenty rats (90-170 g) were grouped into five (A-E) (n = 4) with the approval of the research ethics committee. Materials and Methods: Group A (control) received 0.5 mL of normal saline, Groups B to E received PHZ, PHZ + Astymin (0.5 mL), PHZ + J. secunda (0.2 mg/kg) and PHZ + J. secunda (0.5 mg/kg), respectively. All animals in Groups B to E received 2 mg/kg PHZ intraperitoneally for 2 days, and thereafter, administration of Astymin and J. secunda commenced in Groups C, D and E for 14 days using gavage. Statistical Analysis Used: The data were analysed using a one-way analysis of variance and the Bonferroni post hoc test. Results: Follicle-stimulating hormone (FSH) decreased significantly in PHZ, PHZ + Astymin and PHZ + J. secunda (0.2 mg/kg) and increased significantly in PHZ + J. secunda (0.5 mg/kg) than control. Luteinising hormone (LH) and testosterone significantly (P < 0.001) reduced in treated groups than control. Total cholesterol, triglyceride, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol and very-low-density lipoprotein-cholesterol were significantly reduced in the treated groups than the control. Tumour necrosis factor alpha (TNF-α) significantly (P < 0.001) increased in treated groups than in control. Testicular glutathione (GSH), glutathione peroxidase, catalase and malondialdehyde significantly increased in extract-treated groups compared to control. Superoxide dismutase significantly decreased in PHZ-treated group than in the control. Conclusion: PHZ administration caused testicular toxicity and altered biochemical markers, astymin treatment reduced male reproductive hormones, while J. secunda (0.5 mg/kg) increased FSH and LH, decreased TNFα levels and altered the concentration of testicular antioxidant markers. These alterations may be linked to the toxic effect of PHZ and could negatively affect spermatogenesis.